2019
DOI: 10.26440/ihrj.v2i10.189
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge Regarding Osteoporosis Among Female Medical Students at King Faisal University, Saudi Arabia

Abstract: Introduction: Osteoporosis is a worldwide public health problem that affects both male and females. It is a silent progressive disorder that affects the skeletal system and leads to diminished bone density and fracture. Therefore, awareness, attitude, and practices of people about osteoporosis contribute significantly to primary prevention and early detection of disease. Objective: the present study conducted to assess the knowledge of the female medical students at King Faisal University about osteoporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This result was contradictory to that reported by AlHarthi et al 2017 (20) who found that about two thirds of study subjects had good knowledge. Another opposite nding was reported by Shahi etal 2018 (21) where most study participants had satisfactory knowledge.…”
Section: Discussionmentioning
confidence: 69%
“…This result was contradictory to that reported by AlHarthi et al 2017 (20) who found that about two thirds of study subjects had good knowledge. Another opposite nding was reported by Shahi etal 2018 (21) where most study participants had satisfactory knowledge.…”
Section: Discussionmentioning
confidence: 69%